Sputum induction: review of literature and proposal for a protocol - Scheicher, Marcos Eduardo; Terra Filho, João; Vianna, Elcio Oliveira (São Paulo Medical Journal, 2003)
Since the 1980s, sputum induction by inhalation of hypertonic saline has been successfully used for diagnosing Pneumocystis carinii pneumonia in patients infected with HIV. In recent years, sputum induction and its subsequent processing has been refined as a noninvasive research tool providing important information about inflammatory events in the lower airways, and it has been used for studying various illnesses. In asthma, one application is to use sputum inflammatory indices to increase our understanding of complex relationships between inflammatory cells, mediators, and cytokine mechanisms. In chronic obstructive pulmonary disease, sputum assessment could be used as a screening test before deciding on long-term corticosteroid treatment. In tuberculosis, sputum induction is a valuable diagnostic tool for HIV-seropositive patients who do not produce sputum. Sputum induction appears to be a relatively safe, noninvasive means of obtaining airway secretions from subjects with cystic fibrosis, especially from those who do not normally produce sputum. Moreover, sputum induction can also be used in chronic cough and lung cancer. Generally, induction is performed through ultrasonic nebulizers, using hypertonic saline. It is recommended that sputum be processed as soon as possible, with complete homogenization by the use of dithiothreitol. We have also shown in this article an example of a protocol for inducing and processing sputum employing a nebulizer produced in Brazil.